Type 3 fimbriae among enterobacteria and the ability of spermidine to inhibit MR/K hemagglutination. - Gerlach, G F (1989)
The distribution of the gene cluster encoding type 3 fimbriae among various isolates of the family Enterobacteriaceae was investigated by using 112 clinical and nonclinical isolates. Closely related DNA sequences were detected in all Klebsiella strains, in most Enterobacter isolates, in a smaller number of Escherichia coli and Salmonella spp., and in a single isolate each of Yersinia enterocolitica and Serratia liquefaciens but not in isolates of Morganella or Providencia species or Serratia marcescens. Except for E. coli and Salmonella strains, the presence of gene sequences was correlated with the phenotypic expression of either the MR/K hemagglutinin or fimbriae that reacted with specific antibodies. In one isolate of Y. enterocolitica the expression of type 3 fimbriae was plasmid determined. The polyamine spermidine was identified as an inhibitor of MR/K hemagglutinating activity, exhibiting an MIC of 1.2 mM. Spermidine inhibited the hemagglutination of 37 MR/K-positive clinical isolates from various genera. However, one clinical isolate of Enterobacter cloacae and most (four of five) nonclinical Klebsiella isolates were not completely inhibited.